(3GdOQQ GdaQGFO aj TQM cJGH GdbdGFO aj JUMjM GdYbGFOs - (3CMeO Hf jMji Hf GdeQJVj Hf eaVd Hf efUhQ GdMSfj, GdegOj dOjf Gddg,J (B840 (3g` s ((3eMeO Hf YHO GdQMef s)
(3ChdgG (B:s
(3hajg cJH ChdgG cJGH GdJhMjO , hbHd GdTQhY ajg jfHZi CSfJcde ai ebOeI JJVef CQHYI aUhd (B: (3GdChd s
(3BNQgG (B:s
(3aESJbUi eGbjd ajgG MPQkG ef Pdc , hfSCd Gddg GdJKHJ ai Gdbhd hGdYed hHJeGe gPg GdLedI Je GdSaQ GdChd ef cJGH hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B269 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B206s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
Keywords: (3Gdabg GdESdGejs